DAMPAK HARGA TANDAN BUAH SEGAR (TBS) TERHADAP KESEJAHTERAAN PETANI KELAPA SAWIT (Elaeis Guineensis Jacq) (Studi Kasus Di Koperasi Unit Desa Makarti Tama, Kecamatan Kamang Baru, Kabupaten Sijunjung) - Hamdilah, Kudril; Alatas, Andi; Jarlis, Roni (LPPM Universitas Malikussaleh - Indonesia, 2024)
ABSTRACTThis study aims to analyze fluctuations in the price of TBS on the walfare of elaeis guineenses jacq farmers in Markati Tama (KUD), Kamang Baru District, Sijunjung regency. The method used is a simple linear regression analysis method assisted by SPSS (Statistical Package For Social Science) 25 software, with a sample of 67 sample farmers. The result of this study indicate that : based on the test result for the coefficient of determinations, it was found that the price of elais guineenses jacq TBS had an effect of 87 %. This states that the price of elaies guineenses jacq TBS affect the level of walfare of farmer, especially oil plam farmers in KUD Markati Tama. Then the impact of fluktuations in the variabel price of Fresh Friut Bunches (TBS) on the walfare of elaeis guineenses jacq farmers which can be seen from the results of partial T-test with a t-count value of 32,054 > t-table 0.240, and a sig value of 0,000, then H0 = rejected so that there is a significant influence significant defference between the dependent variabel or price (variable X) with the dependent variabel of walfare (variable Y). Keywords : Elaies Guineenses Jacq Fresh Friut Bunch Price, Fresh friut Bunch Price Fluctuations, Walfare of Elaies Guineenses Jacq Farmers.